2012
DOI: 10.1007/s10661-012-2636-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal availability and sensitivity of two field-collected mayflies for the development of a standardized toxicity test

Abstract: Ecologically relevant toxicity tests may provide the best protection of sensitive aquatic fauna, but without established culturing or test methodology for such organisms, results may be unreliable and difficult to repeat. Further, field-collected organisms may not be feasible for routine testing purposes, as often required for permitted discharges. This study examined the feasibility of testing two field-collected mayflies, Isonychia bicolor and Maccaffertium spp., over a 1-year period. Seasonal comparisons of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The maximum allowable toxicant concentrations for survival and molting endpoints ranged from 1410 mg Cl/L to 3798 mg Cl/L (calculated from salt concentrations). Echols et al observed a mean Isonychia bicolor 7‐d NOEC of 855 mg Cl/L at 20 °C to 23 °C. Goetsch and Palmer reported a 96‐h LC50 between 1500 mg Cl/L and 2500 mg Cl/L for Tricorythus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum allowable toxicant concentrations for survival and molting endpoints ranged from 1410 mg Cl/L to 3798 mg Cl/L (calculated from salt concentrations). Echols et al observed a mean Isonychia bicolor 7‐d NOEC of 855 mg Cl/L at 20 °C to 23 °C. Goetsch and Palmer reported a 96‐h LC50 between 1500 mg Cl/L and 2500 mg Cl/L for Tricorythus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Nominal chloride concentrations for the treatments were as follows: 37 mg Cl -/L (control), 70 mg Cl -/L, 112 mg Cl -/L, 196 mg Cl -/L, 364 mg Cl -/L, and 700 mg Cl -/L. Nominal N-NO 3 concentrations were as follows: 0 mg N-NO 3 /L, and 1300 mg SO 4 2-/L. Test conditions are summarized in Table 2.…”
Section: Chronic Toxicity Testing Proceduresmentioning
confidence: 99%
“…The need therefore exists to develop additional model organisms that may be more representative of native fauna and whose use could better elucidate the underlying mechanisms of ion sensitivity. Although several toxicology studies have used field‐collected Ephemeroptera, Plecoptera, and Trichoptera taxa e.g., and have evaluated that approach as a standardized method , such studies can be hampered by lack of organism availability at certain times of year and by variability in organism sensitivity . The parthenogenetic mayfly Neocloeon triangulifer (formerly Centroptilum triangulifer ) has been reared successfully in a stream‐side laboratory and used in subsequent toxicity testing .…”
Section: Introductionmentioning
confidence: 99%
“…In their study of the effects of imidacloprid on insects in a stream mesocosm, Mohr et al observed a significant decline in numbers of Ephemeroptera, stocked in late May, starting 50 to 60 d later (i.e., from late July onward). Echols et al , assessing the suitability of 2 mayfly species for whole effluent testing, also reported reduced availability of 2 bivoltine native North American mayfly species, in June and July.…”
Section: Discussionmentioning
confidence: 99%